To Investigate or Not to Investigate? Researchers' Views on Unexplored Atmospheric Light Phenomena - Caron, Etienne; Faridi, Pouya (Frontiers in Earth Science, 2016)
For hundreds of years, scientists have been studying light, which is used nowadays to explore the universe and cure diseases. Here, we present the results of a survey indicating a significant support from a subset of the academic community to investigate rare, unusual and unexplained atmospheric light phenomena that have historically been unexplored by scientists — the transient luminous phenomena in the valley of Hessdalen in Norway in particular. We propose that stable, long-term funding, and thorough investigation of poorly understood and/or unexplored luminous phenomena occurring in the low atmosphere could lead to the creation of new inter-disciplinary research programs in multiple universities, and ultimately, to important fundamental discoveries in the field of atmospheric science, photonics and beyond.